2021
DOI: 10.3897/neobiota.67.59185
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of biological invasions in Brazil: a first assessment

Abstract: Biological invasions are one of the leading causes of global environmental change and their impacts can affect biodiversity, ecosystem services, human health and the economy. Yet, the understanding on the impacts of invasive alien species is still limited and mostly related to alien species outbreaks and losses in agricultural yield, followed by the understanding of the ecological impacts on natural systems. Notably, the economic impacts of biological invasions have rarely been quantified. Brazil has at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 106 publications
0
26
0
4
Order By: Relevance
“…The differences amongst the costs found here and other country-level assessments in the region are due to different methodological choices. Adelino et al (2021) found a higher accumulated cost than us for Brazil because they did not remove entries from the original InvaCost dataset (USD 105.5 billion vs. USD 76.8 billion). For the same reason, Duboscq-Carra et al (2021) found an accumulated cost USD 5.5 million higher than us for Argentina (USD 6,907.6 million vs. USD 6,902.1 million).…”
Section: General Patternsmentioning
confidence: 67%
See 1 more Smart Citation
“…The differences amongst the costs found here and other country-level assessments in the region are due to different methodological choices. Adelino et al (2021) found a higher accumulated cost than us for Brazil because they did not remove entries from the original InvaCost dataset (USD 105.5 billion vs. USD 76.8 billion). For the same reason, Duboscq-Carra et al (2021) found an accumulated cost USD 5.5 million higher than us for Argentina (USD 6,907.6 million vs. USD 6,902.1 million).…”
Section: General Patternsmentioning
confidence: 67%
“…In addition, although our study is the first regional assessment in Central and South America and was based on the most upto-date database, we highlight that the costs reported here are a conservative baseline. We did not include cost entries classified as low reliability or reporting expected-only costs in the analysis and there were no published costs for some relevant invasive alien species in the region (e.g., Pterois volitans and Tubastraea coccinea; Adelino et al 2021); furthermore, it is difficult to disentangle costs associated with multiple practices (e.g., restoration; Brancalion et al 2019). Hence, the economic cost of biological invasions in the region is higher and must be evaluated continuously.…”
Section: General Patternsmentioning
confidence: 99%
“…Contrary to other countries in the region -whether mega-diverse or not (Heringer et al 2021;Adelino et al 2021;Duboscq-Carra et al 2021), Ecuadorian institutional authorities, at least in the Galapagos Islands, have invested actively in invasive species management actions. One of the reasons is the body of research about the massive impact that invasive species have on the Galapagos resident biota (Jäger et al 2009;Jäger et al 2013;Rivas-Torres and Rivas 2018;Cooke et al 2020), triggering investment to control or eradicate these species.…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture, for instance, is an important sector that makes up 33.9% of the employment in rural areas of Ecuador (which is higher than the 24% reported in other Andean countries of the region (Martínez Valle 2017). It was also the most impacted activity sector by invasive alien species in Brazil (Adelino et al 2021) and Argentina (Duboscq-Carra et al 2021), while fisheries was ranked first for Mexico (Rico-Sánchez et al 2021). In fact, the scarcity of scientific reports on the economic impacts of invasive species from mainland Ecuador makes it difficult to assess the real cost on most activity sectors.…”
Section: Limitations and Ways Forwardmentioning
confidence: 99%
“…For instance, agricultural losses and damage were the main component of reported costs for Africa (Diagne et al 2021b), the Americas (Crystal-Ornelas et al 2021;Heringer et al 2021), and Asia (Kirichenko et al 2021;Liu et al 2021;Watari et al 2021). Human health costs were strongly related to mosquitoes of the genus Aedes and were a main component of reported costs for Brazil (Adelino et al 2021), Central America (Heringer et al 2021) and Singapore (Haubrock et al 2021b). Conversely, economic costs of preventing or mitigating alien species impacts on biodiversity and ecosystem services were virtually non-existent, with a few exceptions.…”
mentioning
confidence: 99%